The relationship between alopecia areata and alexithymia, anxiety and depression: A case-control study - Rim Sellami; J Masmoudi; U Ouali; L Mnif; M Amouri; H Turki; A Jaoua (Wolters Kluwer Medknow Publications, 2014)
Background: Alopecia areata (AA) is a skin disease characterized by the sudden appearance of areas of hair loss on the scalp and other hair-bearing areas, but its aesthetic repercussions can lead to profound changes in patient's psychological status and relationships. Aim: The goal was to investigate a possible relationship between AA and alexithymia as well as two other emotional dimensions, anxiety and depression. Materials and Methods: Fifty patients with AA seen in the Department of Dermatology of Hedi Chaker University Hospital, Sfax were included in this study. Anxiety and depression were evaluated by Hospital Anxiety and Depression scale questionnaire, alexithymia was assessed by Toronto Alexithymia scale 20, and severity of AA was measured by Severity of Alopecia Tool. Results: Patient's mean age was 32.92 years. 52% of patients were females. Depression and anxiety were detected respectively in 38% and 62% of patients. There was statistically significant difference between patients and control group in terms of depression (P = 0.047) and anxiety (P = 0.005). Forty-two percent of patients scored positive for alexithymia. No significant difference was found between patient and control groups (P = 0.683) in terms of alexithymia. Anxiety was responsible for 14.7% of variation in alexithymia (P = 0.047). Conclusions: Our study shows a high prevalence of anxiety and depressive symptoms in AA patients. Dermatologists should be aware of the psychological impact of AA, especially as current treatments have limited effectiveness.